68.6k views
11 votes
Can i have some help? i'm kinda desperate AND please NO fake answers don't answer if you will give a fake answer

btw if you want an extra 50 points or more you could maybe help with another question i asked recently on my profile as not all of them received applicable answers

Can i have some help? i'm kinda desperate AND please NO fake answers don't answer-example-1

2 Answers

10 votes

Explanation:

Vertex form is:
a(x-h)^2+k

a)
a(x+2)^2+3=y

To find a, plug (-4,1) in for x and y.


a(-4+2)^2+3=1


4a=-2


a=-1/2

so a) is
(-1)/(2) (x+2)^2+3

b) .... I'm not sure what the second coordinate is.

c)
a(x+2)^2-3

Plug in (-5,6) for x and y.


6=a(-5+2)^2-3


9=9a


a=1

so c) is
(x+2)^2-3

d)
a(x+2)^2+5

Plug (1,-4) in for x and y.


-4=a(1+2)^2+5


-9=9a


a=-1

so d) is
-(x+2)^2+5

User Trallnag
by
5.1k points
8 votes

Answer:


\textsf{(a)}\quad y=-(1)/(2)(x+2)^2+3


\textsf{(b)}\quad y=a(x+1)^2-1


\textsf{(c)}\quad y=(x+2)^2-3


\textsf{(d)}\quad y=-(x+2)^2+5

Explanation:

Vertex form


y=a(x-h)^2+k

where (h, k) is the vertex

-------------------------------------------------------------------------------------------

Part (a)

Given: vertex at (-2, 3) passes through (-4 ,1)

Substituting the given vertex into the equation:


\implies y=a(x-(-2))^2+3


\implies y=a(x+2)^2+3

Substitute the given point into the equation to find a:


\implies 1=a(-4+2)^2+3


\implies 1=4a+3


\implies a=-(1)/(2)

Substitute the found value of a to form the final equation:


y=-(1)/(2)(x+2)^2+3

-------------------------------------------------------------------------------------------

Part (b)

Given: vertex at (-1, -1) passes through ?)

Substituting the given vertex into the equation:


\implies y=a(x-(-1))^2+(-1)


\implies y=a(x+1)^2-1

Substitute the given point into the equation to find a:

**no point given**

-------------------------------------------------------------------------------------------

Part (c)

Given: vertex at (-2, -3) passes through (-5, 6)

Substituting the given vertex into the equation:


\implies y=a(x-(-2))^2+(-3)


\implies y=a(x+2)^2-3

Substitute the given point into the equation to find a:


\implies 6=a(-5+2)^2-3


\implies 6=9a-3


\implies a=1

Substitute the given point into the equation to find a:


y=(x+2)^2-3

-------------------------------------------------------------------------------------------

Part (d)

Given: vertex at (-2, 5) passes through (1, -4)

Substituting the given vertex into the equation:


\implies y=a(x-(-2))^2+5


\implies y=a(x+2)^2+5

Substitute the given point into the equation to find a:


\implies -4=a(1+2)^2+5


\implies -4=9a+5


\implies a=-1

Substitute the given point into the equation to find a:


y=-(x+2)^2+5

User ATony
by
5.7k points